KNOWLEDGE SHARING AND THE SUSTAINABLE DEVELOPMENT GOALS: A PERSPECTIVE FROM BRAZILIAN RESEARCHERS - Ziviani, Fabricio; da Silva, Adriana Ferreira; Gonçalves, Carlos Alberto; de Melo, Flávio Ferreira; dos Anjos, Priscila Caneparo; Araújo, Ricardo Alexandre dos Santos; Barreto, Adriano Cardoso; de Oliveira, Silvana Alves (Seven Editora, 2025)
This article discusses the relevance of knowledge sharing in the context of the Sustainable Development Goals (SDGs) of the 2030 Agenda, focusing on the work of Brazilian researchers. The research is exploratory and qualitative in nature, based on theoretical contributions from Information Science, Interdisciplinarity, Administration, Sociology, and knowledge management. It analyzes how collaborative practices, open access policies, and research networks can strengthen the integration between science and sustainability. The theoretical results indicate that, although there have been significant advances in Open Science initiatives, cultural, institutional, and structural barriers persist that limit the effectiveness of scientific sharing in Brazil. It concludes that promoting knowledge sharing represents not only a strategy for innovation and equity, but also an ethical commitment to global sustainability. DOI: https://doi.org/10.56238/sevened2025.036-073